Implementing The Hidden Curriculum in EFL Classroom - Lukman Lukman (Institut Agama Islam Negeri Palopo, 2019)
This research aimed to determine the implementation of the hidden curriculum in EFL learners’ interest. This research was conducted in AL-FITYAN Senior Hight School Gowa. Qualitative approach employed in this study. More specifically, this research employed the descriptive qualitative method. Data collection procedures in this study were the observation, recoding, and interview. Based on the research, it can be seen that the spiritual-cultural aspect of hidden curriculum was implemented in the first class. The findings show that the teacher employed some elements in implementing the hidden curriculum in term of spiritual-cultural aspect. (1) Giving advice and guidance, (2) providing inspiring story and utterance, and (3) applying exemplary. Furthermore, the effects of hidden curriculum implementation can emerge learners’ awareness so that they can be happy, enthusiastic, focus, and avoid their resistance in learning. The result of that, can stimulate the learners’ interest and then construct their attention and motivation.